Economic aspects of conflicts in the global economy in the conditions of the New Cold War - Оlena Baula; Оksana Urban (Економічний форум)
The article summarizes the issue of the main economic aspects in the context of the current increase in the level of world tension, called by some scientists and politicians the «new cold war». The main goal is to study past conflicts and compare them with the current geopolitical situation, in order to determine the causes and nature of the modern phenomenon of economic conflict and its connection with the political situation, predict the further development of world events and describe the problems and prospects for the EU and Ukraine in this context. The systematization of literary sources and approaches to the solution of the researched problem shows that, despite the diversity and content of the approaches around the issues of the forms of influence of globalization on the sources of conflict, the issue of monitoring economic conflicts between the main economic centers of the world in the context of political conflicts of the 21st century remains insufficiently studied, as well as outlining the prospects of European integration of Ukraine in the conditions of Russian aggression. The methodological basis of the research is the methods of scientific abstraction, dialectical analysis, logical-structural and systemic approaches to assessing the economic aspects of confrontations in the world economy. The object of research is the paradigmatic foundations of the Cold War of past periods and the present. The article empirically confirms that the beginning of the 21st century. there are three economic centers: the United States is the only superpower after the Cold War; The EU is an independent global economic entity; China is the second largest economy in the world and the «factory of the world». An attempt was also made to analyze the effectiveness of sanctions for the Russian Federation as a tool for economic warfare and their impact on key global markets. It is assumed that in order to ensure the strength of the EU's own governance system, it is advisable to implement priorities related to overcoming inequality by guaranteeing the sustainable development of the region, as well as the revival of the Western European security order to guarantee peace and stability in its countries and Ukraine. The results of the study can be useful for the development of scientifically based recommendations for improving the economic mechanisms of influence on the aggressor countries